Two tales the call to hajj , the she-camel - Khan, Saniyasnain (GoodwordKidz New Delhi, 2004)
The first tale emphasizes the significance of the Hajj pilgrimage and the spiritual journey it represents. The second story features the miraculous she-camel sent as a sign, highlighting themes of faith and obedience.